CHOOSING A CAREER AS A PUBLIC ACCOUNTANT: DOES CALLING MATTER? - Dhita Mawar Hutami; Muamar Nur Kholid; Selfira Salsabilla (JRAK, 2022)
Public accountants are in great demand in Indonesia. However, the development of the new public accountant did not go as planned. This study aims to determine the antecedents that influence accounting students' intention to pursue careers as public accountants. This study's Social Cognitive Career Theory (SCCT) framework is extended by adding a Role Model and Calling. The participants in this study are 204 accounting students who have taken the auditing course. The findings of this study reveal that calling has a significant positive effect on accounting students' outcome expectations and intention to pursue careers as public accountants. The role model significantly affects self-efficacy and intention to pursue a career as a public accountant. Regrettably, outcome expectancy does not affect a student's intention. This study discusses the practical consequences of encouraging students to choose careers as public accountants through data analysis.